District Plan 1958-59 Khammam District Government of Andhra Pradesh - Planning Commission (Planning Commission, 1958)
The aim of the scheme is to produce 20,00 additional bales of 392 lbs of each, during the second plan period by the application of scientific methods of cultivation and the use of improved seeds and adoption of plant protection measures. During the current year, it is proposed to cover an area of 62400 acres net and produce 23500 additional bales of cotton for which a sum of Rs 1.42 lakhs has been provided In the plan for the year 1958-59. Of this, 3 additional bales of cotton are expected to be produced over an area of 5 acres in this district.
Planning and Development Department
Planning and Development Department Government of Andhra Pradesh